Burden of Important Risk Factors for Common Cancers Among Older Adults in Markazi Province, Iran in 2016 - Ahmad Amani; Ahmad Ali Akbari Kamrani; Reza Fadayevatan; Babak Eshrati; Mohammad Rafiee (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives The burden of disease analysis can be used to measure the factors that are suitable for interventions for disease control. This study aims to calculate the burden of risk factors for common cancers among the elderly in Markazi Province of Iran in 2016. Methods & Materials This a retrospective descriptive-analytical study. Information was collected based on age and sex groups, which included the cancer incidence rate, cancer death rate, cancer disability rate based on the GBD standard table, which were collected from the website of Statistics Centre of Iran, the latest death report and the latest cancer report in 2016. The data analyses were done in Excel and DISMOD2 applications. The disease burden calculation formula was used in this study. To ensure the validity and reliability of the data, the data with wrong or useless codes were excluded. Results For skin cancer, the highest burden was related to exposure to sunlight (526.71); for stomach cancer, family history (79305.88); for colon, lack of fruit consumption (4063.18); for breast cancer, lack of marriage (6488.58); and for prostate cancer, history of previous diseases (7244.08). Conclusion Family history of cancer, smoking, obesity, and physical inactivity are common risk factors of most cancers with a same burden.